Optimization of o-cresol degrading microorganism and kinetics of degradation - Krishnan Nhattuketty Shainy; Rajamanickam Usha (Universitas Gadjah Mada, 2018)
In the present study, Pseudomonas monteilii CR13 isolated from petroleum contaminated soil demonstrated the highest specific o-cresol degradation rate at all tested o-cresol concentrations and also was not disturbed by the starting substrate concentration used (o-cresol-500 mg/L). After a serial transfer of the isolate into a series of increasing o-cresol level, the organism demonstrated significant improvement on degradation ability up to 3000 mg/L. The optimum condition for the cell mass increase and biodegradation of o-cresol by Pseudomonas monteilii was in the minimal mineral medium of 3 at a pH of 6.5 and temperature 30 °C, stirring velocity of 160 rpm, and the substrate concentration of 500 mg/L. The biodegradation kinetic study was carried out by bacteria in different initial substrate concentrations (500–3000 mg/L). In the present test the μmax, Ks and the μ were found 0.332 h-1, 0.166 mg/L and 0.0282 mg/L for 500 mg/L of o-cresol, respectively. The organism is highly promising and could be used to remove high concentrations of o-cresol from highly polluted aquatic and soil regions. The cells could be immobilized on a suitable matrix and the efficiency of degradation could be effectively improved.